Willingness to pay of the native chicken eggs in urban supermarket: evidence from Semarang, Indonesia - Desy Wulandari; Wiludjeng Roessali; Kustopo Budiraharjo (Publisher of Widyagama University of Malang (UWG Press), 2020)
Urban people show a certain preference in consuming native chicken eggs products. This research aims to identify market segmentation and analyze willingness to pay (WTP) for consumers of native chicken eggs. The research was conducted at four places in the supermarket in Semarang city. Respondents as many as 100 people were selected using an accidental sampling method. Data were analyzed by descriptive and Contingent Valuation Method (CVM). The results show that consumer market segmentation can explain the analysis of WTP. Marked characteristics of consumers of the native chicken egg include in between 25-50 years old (50%), female (89%), go shopping as family motivation (70%), and purchasing once a week (85%). 87% of respondents show the WTP in the range of 5 to 20% above the existing price. The maximum WTP is 23.45 thousand rupiahs per pack. The highest of maximum WTP found in rattan packaging in Superindo is 26.79 thousand rupiahs per pack. The highest WTP aggregation value is found in Gelael with mica packaging at the 373 thousand rupiahs. Furthermore, supermarkets can contribute to apply quality standards for native chicken eggs, and protect the interests of consumers.JEL Classification: D12, Q02; Q13